2014
DOI: 10.4103/0189-6725.137334
|View full text |Cite
|
Sign up to set email alerts
|

Complications of peripherally inserted central venous catheters in neonates: Lesson learned over 2 years in a tertiary care centre in India

Abstract: Precautions should be taken and position must be confirmed during and after PICC insertion to avoid undue complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Other common complications of PICC placement include blockage, leakage, thrombosis, and pneumothorax [10] . However, pneumothorax rarely occurs in infants with the PICC line [15] . Pneumothorax refers to the presence of air in the pleural cavity that may occur spontaneously or as a result of trauma [16] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other common complications of PICC placement include blockage, leakage, thrombosis, and pneumothorax [10] . However, pneumothorax rarely occurs in infants with the PICC line [15] . Pneumothorax refers to the presence of air in the pleural cavity that may occur spontaneously or as a result of trauma [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Positive pleural pressure is a life-threatening condition since it causes severe ventilatory impairment so that the positive pressure is transmitted to the mediastinum, resulting in reduced venous return and decreased cardiac output [16] . Pneumothorax may occur during lung biopsy or pleural drainage due to the perforation of the visceral pleura and the leakage of air into the lungs [15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such complications can cause an increase in the costs of health services due to the increase in the length of stay in the NICU, as well as injuries to NBs, such as tissue, cardiological, and infectious injuries. Previous studies on complications related to the use of PICC in NBs have demonstrated the prevalence of tissue complications (edema, phlebitis, enlargement, and necrosis) and systemic complications (arrhythmias, cardiac tamponade, and sepsis) [3,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is claimed that the use of a PICC may result in embolization, cardiac tamponade, or pleural effusion. Although rare, these complications are potentially life-threatening [15,18]. According to the data of various studies, 41–50% of PVCs are removed or changed as a result of complications, the most common being local infiltration, extravasation, or occlusion [11,19].…”
Section: Introductionmentioning
confidence: 99%